2021
DOI: 10.3390/antiox10020157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antioxidant and Anti-Inflammatory Capacity of Diet on Psoriasis and Psoriatic Arthritis Phenotype: Nutrition as Therapeutic Tool?

Abstract: Chronic inflammation and increased oxidative stress are contributing factors to many non-communicable diseases. A growing body of evidence indicates that dietary nutrients can activate the immune system and may lead to the overproduction of pro-inflammatory cytokines. Fatty acids as macronutrients are key players for immunomodulation, with n-3 polyunsaturated fatty acids having the most beneficial effect, while polyphenols and carotenoids seem to be the most promising antioxidants. Psoriasis is a chronic, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 240 publications
(100 reference statements)
1
53
0
6
Order By: Relevance
“…In an overview of food, therapeutic and industrial applications of Brazilian fruits of Arecaceae family, de Souza et al considered açaí, from the physicochemical perspective, as a good supplement in the human diet due to its high content of compounds with known pharmacological properties and/or health benefits [ 35 ], such as oleic acid [ 36 ], anthocyanins [ 37 ], carotenoids [ 38 ] and phenolic compounds [ 39 ]. These compounds are related to the powerful antioxidant activity of berries [ 40 ] and other underused wild plants seeds [ 41 ] such as the acai seed.…”
Section: Discussionmentioning
confidence: 99%
“…In an overview of food, therapeutic and industrial applications of Brazilian fruits of Arecaceae family, de Souza et al considered açaí, from the physicochemical perspective, as a good supplement in the human diet due to its high content of compounds with known pharmacological properties and/or health benefits [ 35 ], such as oleic acid [ 36 ], anthocyanins [ 37 ], carotenoids [ 38 ] and phenolic compounds [ 39 ]. These compounds are related to the powerful antioxidant activity of berries [ 40 ] and other underused wild plants seeds [ 41 ] such as the acai seed.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case of PP induced by cytokines, interferon-c, interleukin-17, and tumor necrosis factor-a in various diseases, it has been suggested that ketogenic diets can be a therapeutic option for psoriasis. 2 Conversely, PP was provoked by ketogenic diet in our psoriasis patient. The pathogenesis of PP is still unclear.…”
mentioning
confidence: 70%
“…Similarly, the anti-inflammatory effects of diet on psoriasis could be explained by beneficial mechanisms mainly exerted by a dietary component such as oleic acid, monounsaturated fatty acids, polyphenols, dietary fibers, anti-oxidant agents, and micronutrients (Katsimbri et al 2021). Additionally, a particular diet may change the gut microbiota and thus elicit unwanted and aggravated immune function (e.g., modification of the T helper cell, T-regulatory cell, and type 17 and its balance) which can activate systemic autoimmune diseases (Chow and Mazmanian 2009).…”
Section: Discussionmentioning
confidence: 99%